2018
DOI: 10.3390/rs10091440
|View full text |Cite
|
Sign up to set email alerts
|

Scale Matters: Spatially Partitioned Unsupervised Segmentation Parameter Optimization for Large and Heterogeneous Satellite Images

Abstract: To classify Very-High-Resolution (VHR) imagery, Geographic Object Based Image Analysis (GEOBIA) is the most popular method used to produce high quality Land-Use/Land-Cover maps. A crucial step in GEOBIA is the appropriate parametrization of the segmentation algorithm prior to the classification. However, little effort has been made to automatically optimize GEOBIA algorithms in an unsupervised and spatially meaningful manner. So far, most Unsupervised Segmentation Parameter Optimization (USPO) techniques, assu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 67 publications
(101 reference statements)
1
47
0
Order By: Relevance
“…An important advantage of the proposed method is its potential for automation with particular merit for large, heterogeneous areas. As Grippa et al [47] and Georganos et al [48] pointed out, in heterogeneous urban scenes a single set of segmentation parameters is inadequate and less efficient than spatially partitioning the study area into several subsets and optimizing each separately. Similar studies for semi-rural and agricultural environments have demonstrated the efficacy of local optimization through the use of F-measure and ESP methods [25,27].…”
Section: Discussionmentioning
confidence: 99%
“…An important advantage of the proposed method is its potential for automation with particular merit for large, heterogeneous areas. As Grippa et al [47] and Georganos et al [48] pointed out, in heterogeneous urban scenes a single set of segmentation parameters is inadequate and less efficient than spatially partitioning the study area into several subsets and optimizing each separately. Similar studies for semi-rural and agricultural environments have demonstrated the efficacy of local optimization through the use of F-measure and ESP methods [25,27].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to properly assess the performance of the tested machine learning algorithms (CNN and RF), the significance of the overall accuracy between classifications was calculated using the McNemar statistical test [65,66]. Several studies have reported the use of the McNemar test to compare between two classification approaches [54,67,68]. In this test, a null hypothesis that there is no significant difference between OA values of the two compared classifications is proposed.…”
Section: Inter-comparison and Quality Assessmentmentioning
confidence: 99%
“…However, even in state-of-the-art methods, the segmentation parameters are generally optimized for whole scenes, which is not effective for citywide mapping that involves large images with a high degree of heterogeneity. Therefore, a local segmentation optimization was developed (spatially partitioned unsupervised segmentation parameter optimization [101]) that outperforms global approaches, both in terms of thematic and geometric accuracy [102].…”
Section: The Potential Of Obia For Generating Land Cover Information mentioning
confidence: 99%